2021
DOI: 10.3847/1538-3881/ac0622
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Search for Outbursting AM CVn Systems with the Zwicky Transient Facility

Abstract: AM CVn systems are a rare type of accreting binary that consists of a white dwarf and a helium-rich, degenerate donor star. Using the Zwicky Transient Facility (ZTF), we searched for new AM CVn systems by focusing on blue, outbursting stars. We first selected outbursting stars using the ZTF alerts. We cross matched the candidates with Gaia and Pan-STARRS catalogs. The initial selection of candidates based on the Gaia BP-RP contains 1751 unknown objects. We used the Pan-STARRS g-r and r-i color in combination w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 80 publications
(116 reference statements)
0
16
0
Order By: Relevance
“…This source was found as an outbursting source in ZTF by Szkody et al (2020), and later confirmed via spectroscopy to be an AM CVn by van Roestel et al (2021), who also looked at the outburts properties using ZTF data. Here, we report the observations with TESS.…”
Section: Ztf18abihypgmentioning
confidence: 78%
See 1 more Smart Citation
“…This source was found as an outbursting source in ZTF by Szkody et al (2020), and later confirmed via spectroscopy to be an AM CVn by van Roestel et al (2021), who also looked at the outburts properties using ZTF data. Here, we report the observations with TESS.…”
Section: Ztf18abihypgmentioning
confidence: 78%
“…Both outbursts show similar profiles and duration of the order of one day. van Roestel et al (2021) report for this source a high frequency of outbursts, but during the two contiguous sectors of observation by TESS ( 54 d) we only see one outburst, meaning that for this source the recurrence time for normal outburst is larger than 50 d. The cadence of both sectors was of 30-min, meaning that we could not perform any periodicity search on the outburst to look for possible superhumps or confirm the orbital period. Based on the SO recurrence time, van Roestel et al ( 2021) predict a period of ∼31.2 min, this would imply a long recurrence time for the SO (Levitan et al 2015), and explains why we did not detect any SO in the two contiguous sectors.…”
Section: Ztf18abihypgmentioning
confidence: 88%
“…The Zwicky Transient Facility (ZTF; Kulkarni 2018) has been used prolifically in contemporary transient detection and characterization efforts. Astrophysical transients observed and/ or discovered by ZTF include: tidal disruption events (e.g., van Velzen et al 2021), candidate electromagnetic counterparts to gravitational wave events (e.g., Graham et al 2020), type Ia supernovae (e.g., Yao et al 2019;Bulla et al 2020;Miller et al 2020), dwarf novae (e.g., Soraisam et al 2021), cataclysmic variables (e.g., Szkody et al 2020), AM CvN systems (van Roestel et al 2021a), general stellar variables (e.g., Roulston et al 2021;van Roestel et al 2021b), active galactic nuclei (e.g., Frederick et al 2019;Ward et al 2021), and solar system bodies such as comets and asteroids (e.g., Ye et al 2020bYe et al , 2020a.…”
Section: Introductionmentioning
confidence: 99%
“…Among the ∼1000 WDs observed by the Kepler K2 mission (Howell et al 2014 ), only one new DWD was disco v ered (Hallakoun et al 2016 ;van Sluijs & Van Eylen 2018 , along with one known DWD). The Zwicky Transient Facility (ZTF; Bellm et al 2019 ;Graham et al 2019 ;Masci et al 2019 ), which has begun operating in 2018, shows promising results, with already ∼10 newly disco v ered ultra-compact DWDs (Burdge et al 2019(Burdge et al , 2020aCoughlin et al 2020 ;Keller et al 2022 ; and see also van Roestel et al 2021 for interacting DWDs). In the near future, large all-sky surv e ys such as Gaia (Gaia Collaboration 2016, 2018 and the Vera Rubin Observatory (LSST Science Collaboration 2009 ) have the potential to deliver up to a few hundred and a few thousand of ne w eclipsing DWDs, respecti vely (Eyer et al 2012 ;Korol et al 2017 ).…”
Section: The Search For Dwdsmentioning
confidence: 99%